The Information Needs and Preferences of Persons with Longstanding Inflammatory Bowel Disease - Samantha Wong; John R Walker; Rachel Carr; Lesley A Graff; Ian Clara; Stephen Promislow; Linda Rogala; Norine Miller; Patricia Rawsthorne; Charles N Bernstein (Canadian Journal of Gastroenterology)
BACKGROUND: Understanding the information needs and preferred vehicles of information delivery to patients with inflammatory bowel disease (IBD) will enhance their care.